2021
DOI: 10.48550/arxiv.2109.04487
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing the radial acceleration relation and the strong equivalence principle with the Coma cluster ultra-diffuse galaxies

J. Freundlich,
B. Famaey,
P. -A. Oria
et al.

Abstract: The tight radial acceleration relation (RAR) obeyed by rotationally supported disk galaxies is one of the most successful a priori prediction of the modified Newtonian dynamics (MOND) paradigm on galaxy scales. Another important consequence of MOND as a classical modification of gravity is that the strong equivalence principle (SEP) -which requires the dynamics of a small free-falling self-gravitating system to not depend on the external gravitational field in which it is embedded -should be broken. Multiple t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 154 publications
(284 reference statements)
0
4
0
Order By: Relevance
“…We note that the rotation curve with EFE is very well fit by the formula proposed by Freundlich et al (2021), approximating the average radial acceleration g r (r) over a sphere at a given radius r in a constant external field :…”
Section: Ngc 5055: An Archetypical Galaxy Under a Strong Efementioning
confidence: 65%
See 1 more Smart Citation
“…We note that the rotation curve with EFE is very well fit by the formula proposed by Freundlich et al (2021), approximating the average radial acceleration g r (r) over a sphere at a given radius r in a constant external field :…”
Section: Ngc 5055: An Archetypical Galaxy Under a Strong Efementioning
confidence: 65%
“…Dynamically, the best we can probably hope to achieve is the Keplerian decline of the rotation curve associated to the EFE. With this in mind, we will now study in detail a new formula proposed in Freundlich et al (2021) and compare it to our exact QUMOND calculations.…”
Section: Ngc 5055: An Archetypical Galaxy Under a Strong Efementioning
confidence: 99%
“…Preliminary results suggest a significant problem for ΛCDM because the dwarfs should be immune to tides, but this issue seems to be resolved in MOND where they would be much more eas-ily disrupted. 1 A similar analysis might also be possible in the Coma cluster (Chilingarian et al 2019;Freundlich et al 2021).…”
Section: Tidal Stabilitymentioning
confidence: 84%
“…They have pointed out that these deduced fields are correlated with the large-scale cosmic environments of galaxies, supporting the EFE interpretation of the SPARC data. On the other hand, Freundlich et al (2021) have not found indications of EFE from an analyses of 11 UDGs including those in the Coma cluster (a fact that could, however, be due to their being heated tidally in the cluster), while study of tidally-affected dwarfs in the Fornax cluster found, to the contrary, strong indication that they are subject to the EFE of the cluster (E. Asencio, private communication).…”
mentioning
confidence: 99%